Efficacy of Guduchyadi Yoga in the Management of Medoroga with special reference to Dyslipidemia- A Rondomized Clinical Trial (International Journal of Ayurveda and Pharma Research, 2025)
Medoroga, a condition which arises due to Medo dhatu vriddhi which may lead to Bahutwa and Abaddhatwa of Poshaka medo dhatu. It can be correlated to disease dyslipidemia based on pathophysiology. It is the need of the hour to contribute safer, effective and economical medicines to manage the condition. Main aim of the study was to evaluate the efficacy of Guduchyadi yoga and Navaka Guggulu in the management of Medoroga with special reference to dyslipidemia. Methods: The present study implemented an open-labelled, active controlled pre and post-test clinical study with 30 subjects (who fulfilled the diagnostic and inclusion criteria). A convenience sampling method was used for the selection. Subjects were randomly assigned into two groups, Group A (trial) and Group B (control) comprising of 15 subjects each. Subjects of Group A received Guduchyadi Yoga (50ml Kashaya with 1.5g of Guggulu) and Group B received Navaka Guggulu (2 tablets with warm water). Both interventions were given twice daily before food for duration of 30 days. A twelve-hour fasting sample of serum lipid profile and BMI were used to measure the efficacy before and after the treatment. Statistical analysis of parameters was assessed using Wilcoxon signed rank test (W), Friedman’s test, Mann Whitney U test (U), by paired t-test, repeated measures ANOVA test, unpaired t-test. Results: The trial drug showed statistically significant result in improving serum lipid profile and reducing BMI (P